Pulmonary hypertension and severe right heart failure following lumbar spinal surgery. (May 2019) - Jayasekera, Geeshath; Johnson, Martin; Hussey, Keith; Church, Colin
Pulmonary hypertension is a disease process affecting the pulmonary circulation and is defined by an increase in pulmonary artery pressure subsequently causing right ventricular failure. Vascular complications, including arteriovenous fistulae, are recognised, but are uncommon complications of spinal surgery. Arteriovenous fistulae increase venous return to the right heart and can induce a high-output cardiac state, mimicking pulmonary arterial hypertension and right heart failure. We present a 47-year-old man with a 1 year history of worsening dyspnoea, exertional pre-syncope and leg swelling presenting with severe right heart failure. The previous year, he had complex spinal surgery, which included discectomy, laminectomy and bilateral nerve reconstruction at L5-S1 level. Initial non-invasive investigations including echocardiography and chest imaging raised the possibility of right heart failure presumed secondary to pulmonary vascular disease. Clinical examination and right heart catheterisation were in keeping with a high cardiac output state, and invasive saturation monitoring was suggestive of a sub-diaphragmatic shunt. Subsequent imaging confirmed the presence of an iatrogenic ilio-iliac arteriovenous fistula. The patient underwent urgent endovascular repair, which resulted in resolution of his symptoms and haemodynamics. We describe the case and present a review of the relevant literature.